The Influence of Ease of Use, Usefulness, Trust, Attitude on Intention in Small, Micro and Medium Enterprises in Tangerang - Riki Firmansyah; Candra Putra (Yayasan Gema Bina Nusantara, 2023)
The use of digital wallets as a form of electronic money has become popular in Indonesia, providing benefits for both customers and traders. Digital wallets enable payments via QR code and provide efficiency in financial management. Digital financial systems also increase efficiency and productivity in fund transfers, payments, and investment management. The aim of this research is to see whether digital payments can improve the quality of MSME financial management. To explore the background of the problems listed, a descriptive approach is used. The population in this study was 50 MSMEs in Tangerang City and Tangerang Regency. In this research, the primary data used is the results of filling out questionnaires by research participants. Based on the results of our group analysis, it can be concluded that the factors perceived ease of use, perceived usefulness, trust, and attitude towards digital payment have an impact on the intention to use digital payment and the equitable use of digital payment for Indonesian MSMEs